The Effect of Liquidity and Company Size on the Company Value of the Automotive Subsector on the Indonesia Stock Exchange - Ramlah; Nurfadilah; Luisito Hari Krisanto; Mozes Haryanto Baottong; Maradu Ariguna H (Indonesian Journal of Advanced Research, 2023)
The purpose of this study was to analyze the effect of liquidity and company size on the automotive sub-sector company value on the Indonesian stock exchange. The analytical method used is quantitative descriptive analysis. The analytical tool used is multiple linear regression analysis with statistical tools IBM SPSS version 23.0. The results of the analysis show that partially liquidity has a positive and significant effect on the automotive subsector company value on the Indonesia Stock Exchange and company size has a positive and insignificant effect on the automotive subsector company value on the Indonesia Stock Exchange.